Effects of mother corm diameter and plant growth regulators on ex vitro corm propagule regeneration in saffron (Crocus sativus L.) - Yildirim, Mehmet Ugur; Hajyzadeh, Mortaza (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
Saffron (Crocus sativus L.), is an economically important spice, medicinaland dye plant that is vegetatively propagated through corms. Saffron cormshave low multiplication efficiency under field conditions; therefore, any effort toaccelerate their multiplication will be desired. The study aimed to establish amutiplication system using small (1.10 to 1.75 cm) and large (1.75 to 2.40 cm)diametered mother saffron corms after treatment with 20 mg·L-1 BAP + 300 mg·L-1 GA3 or 20 mg·L-1 BAP for 4, 6, 8, 10 h. The best corm induction rate was noted on treatment with 20 mg·L-1 BAP for 4 h pretreatment irrespective of the mother corm dimeter. Small and large mother corms had maximum multiplication rate of 80.00 and 86.67%, mean number of 6.17 and 5.55 cormlets induction per mother corm with 0.62 and 0.69 cm diameter. All of them induced variable number of roots per corm propagule. The experiment was completed in 90 days. The results show that, pretreatment of saffron corms with BAP + GA3 or BAP could serve as an appropriate technique for economic multiplication of saffron corms without compromising qualitative and quantitative characteristics of saffron. The results obtained in this study could be used to help in designing improved saffron corm production in future.